(untitled) (The Research of Medical Science Review, 2025)
Background: Gestational weight gain (GWG) is a critical factor influencing both maternal and fetal health outcomes during pregnancy. Excessive or inadequate weight gain can lead to complications such as gestational diabetes mellitus (GDM), gestational hypertension, preterm birth, and low birth weight, which significantly impact maternal and neonatal well-being. Understanding the frequency and implications of these outcomes is essential for improving prenatal care and reducing adverse fetomaternal risks. This study aims to evaluate the frequency of fetomaternal outcomes associated with GWG in a tertiary care setting. Objective: To determine the frequency of fetomaternal outcomes in women with gestational weight gain presenting to Khyber Teaching Hospital, Peshawar. Material and Methods: This descriptive case series was conducted from 25th September 2022 to 25th March 2023 at Department of Obstetrics and Gynaecology, Khyber Teaching Hospital, Peshawar. A total of 115 pregnant women with gestational weight gain were included. Patients were followed up until delivery, and fetomaternal outcomes, including gestational diabetes mellitus, gestational hypertension, cesarean section (C-section), preterm birth, low birth weight, and neonatal intensive care unit (NICU) admission, were recorded. Results: The age range of participants was 18 to 40 years, with a mean age of 27.773 ± 3.51 years. The mean gestational age was 26.913 ± 2.58 weeks, mean parity was 1.182 ± 1.47, and mean preconception weight was 67.504 ± 4.93 The frequency of observed outcomes was as follows: gestational diabetes mellitus (27%), gestational hypertension (22.6%), C-section (21.7%), preterm birth (11.3%), low birth weight (10.4%), and NICU admission (25.2%). Conclusion: This study highlights the significant impact of gestational weight gain on fetomaternal outcomes, particularly the association with gestational diabetes mellitus and gestational hypertension. The findings underscore the need for targeted interventions and monitoring during pregnancy to mitigate risks and improve maternal and neonatal health.